Differences in help-seeking tendency in intimate partner violence between Jewish and Arab women in Israel - Ne'eman-Haviv, Vered; Shafran, Yoel (Frontiers in Sociology, 2023)
Objective Intimate partner violence (IPV) has many consequences for the physical and mental health of the victims. One strategy for coping with IPV is to turn to formal and informal sources for help. The purpose of the present study was to examine the differences in help seeking tendency in cases of IPV between Jewish and Arab women in Israel and the connection to their mental health. Method We administered a structured quantitative questionnaire to a sample of 357 Jewish (44.8%) and 439 Arab (55.2%) women. Results The findings indicate that Jewish women tend to seek help more often than do Arab women, and that there are differences in the targets they approach. Jewish women turn more frequently to unofficial sources, such as friends, relatives, and associations, whereas Arab women approach more often official sources such as social workers and clergy. Conclusions We propose an explanation for the differences based on socio-cultural factors. This study illustrates that it is necessary to act with cultural sensitivity and adapt the help options offered to the culture to which the women belong. This adjustment may encourage more women to apply for support to escape the world of violence.